2008
DOI: 10.1002/humu.20707
|View full text |Cite
|
Sign up to set email alerts
|

Frequent mutations in the neurotrophic tyrosine receptor kinase gene family in large cell neuroendocrine carcinoma of the lung

Abstract: The neurotrophic tyrosine receptor kinase (NTRK) family is potentially implicated in tumorigenesis and progression of several neoplastic diseases, including lung cancer. We investigated a large number of pulmonary neuroendocrine tumors (PNETs) and non-small cell lung carcinomas (NSCLCs) without morphological evidence of neuroendocrine differentiation for mutations in the NTRK gene family. A total of 538 primary lung carcinomas, including 17 typical carcinoids (TCs), 10 atypical carcinoids (ACs), 39 small cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 44 publications
1
51
1
1
Order By: Relevance
“…Both the myosin phosphatase Rho-interacting protein (MPRIP)-NTRK1 and CD74-NTRK1 fusions lead to constitutive TRKA kinase activity and have been shown to be oncogenic. In addition, Marchetti et al (7) demonstrated that there are NTRK3 mutations associated with the TRKC receptor and NTRK2 mutations encoding the NTRK2 (TRKB) receptor in lung large-cell neuroendocrine carcinoma (LCNEC). Recently, the TRKB signaling pathway was also reported to be a potential therapeutic target for lung LCNEC (8).…”
Section: Introductionmentioning
confidence: 99%
“…Both the myosin phosphatase Rho-interacting protein (MPRIP)-NTRK1 and CD74-NTRK1 fusions lead to constitutive TRKA kinase activity and have been shown to be oncogenic. In addition, Marchetti et al (7) demonstrated that there are NTRK3 mutations associated with the TRKC receptor and NTRK2 mutations encoding the NTRK2 (TRKB) receptor in lung large-cell neuroendocrine carcinoma (LCNEC). Recently, the TRKB signaling pathway was also reported to be a potential therapeutic target for lung LCNEC (8).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple series have reported 85-98% of patients who had a surgical resection of LCNEC had a history of habitual cigarette smoking [1,2]. Genetic risk factors include mutation of the epidermal growth factor receptor (EGFR) gene or tyrosine kinase domain (TKD) of the neurotrophic tyrosine receptor kinase (NTRK) gene [3,4]. LCNEC can be a challenge to diagnose since patients rarely present with pulmonary symptoms and <20% present with cough or hemoptysis [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Activating genetic translocations involving the linkage of NTRK1 and NTRK3 to various partner proteins have been described in several cancers, most notably in thyroid and secretory breast carcinomas. A growing list of intriguing point mutations in the Trk genes have also been recently reported in primary tumors of various origin (5,6). Whereas the functional consequences of these mutations have yet to be elucidated in most cases, the localization of many of the mutations to key residues of the kinase domain suggests that they could be activating in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Trk receptors have also been shown to be potent oncogenes with roles in malignant transformation, metastasis, and survival signaling in human tumors (3)(4)(5). Independent mechanisms of Trk pathway activation, including constitutive oncogenic fusions, autocrine signaling, and point mutations, have been described in medulloblastoma; neuroblastoma; acute myelogenous leukemia (AML); and thyroid, pancreatic, breast, lung, and prostate cancers, suggesting that the Trk pathway may be more broadly involved in carcinogenesis and tumor cell survival (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%